2016
DOI: 10.1177/0363546516643809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Remnant Tissue Preservation on the Tendon Graft in Anterior Cruciate Ligament Reconstruction

Abstract: These results imply that preservation of the ACL remnant tissue may improve graft healing after ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 40 publications
2
86
1
1
Order By: Relevance
“…58 Healing has been shown to occur, between the remnant and the graft, (between 4 and 12 weeks postreconstruction in a sheep model) with remnant-preservation resulting in both accelerated revascularization and increased MRCs after this time point. 59 Other improvements have been recorded in terms of a thicker synovium (and graft crosssectional area), a wider attachment to the tibia, increased density of blood vessels, and a smaller avascular zone in the center of the graft. 59 Furthermore, Fu et al showed the presence of mesenchymal stem cells, 60 Xie et al found an increase in mRNA expression (associated with angiogenesis and nerve growth), 61 and Trocan et al found the presence of CD-34 positive fibroblasts (required for angiogenesis) within the ACL remnant.…”
Section: Remnant-preservation Acl Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Healing has been shown to occur, between the remnant and the graft, (between 4 and 12 weeks postreconstruction in a sheep model) with remnant-preservation resulting in both accelerated revascularization and increased MRCs after this time point. 59 Other improvements have been recorded in terms of a thicker synovium (and graft crosssectional area), a wider attachment to the tibia, increased density of blood vessels, and a smaller avascular zone in the center of the graft. 59 Furthermore, Fu et al showed the presence of mesenchymal stem cells, 60 Xie et al found an increase in mRNA expression (associated with angiogenesis and nerve growth), 61 and Trocan et al found the presence of CD-34 positive fibroblasts (required for angiogenesis) within the ACL remnant.…”
Section: Remnant-preservation Acl Reconstructionmentioning
confidence: 99%
“…59 Other improvements have been recorded in terms of a thicker synovium (and graft crosssectional area), a wider attachment to the tibia, increased density of blood vessels, and a smaller avascular zone in the center of the graft. 59 Furthermore, Fu et al showed the presence of mesenchymal stem cells, 60 Xie et al found an increase in mRNA expression (associated with angiogenesis and nerve growth), 61 and Trocan et al found the presence of CD-34 positive fibroblasts (required for angiogenesis) within the ACL remnant. 62 Following on from the research covered in the previous section, work (in a sheep model) has demonstrated that adhesion of the remnant to the graft prevents degeneration of neural elements by retensioning this tissue.…”
Section: Remnant-preservation Acl Reconstructionmentioning
confidence: 99%
“…Remnant-preserved ACL reconstruction is gaining popularity because the remnant-preservation effect may have the advantages of synovial coverage of the graft, graft remodeling, proprioceptive recovery, stability, and better clinical outcomes, [14][15][16]29 although controversial reports exist. 30,31 However, most remnant-preserved ACL reconstructions do not repair the remnant.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, remnant-preserved anterior cruciate ligament (ACL) reconstruction has gained popularity because the remnant-preservation effect may be advantageous for graft remodeling, proprioceptive recovery, and clinical outcomes. [14][15][16] We describe the technique of anatomical arthroscopic ATFL repair and reconstruction (AAARR) using a free tendon graft, which has the possible advantages of not only remnant preservation but also sharing of the ligament load by the repaired ATFL remnant and the reconstructed ATFL graft. A summary of the key steps is provided in Table 1, and a summary of the technique is shown in Video 1.…”
mentioning
confidence: 99%
“…к тому же с увеличением вре-мени после травмы происходит его дальнейшее уменьшение [15]. В связи с этим такая тактика может быть перспективной в основном для па-циентов молодого возраста в ранние сроки после травмы [10,16]. однако это положение оспари-вается M.S.…”
unclassified